2002
DOI: 10.1646/0006-3606(2002)034[0547:hftdtn]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Herbivore-Free Time? Damage to New Leaves of Woody Plants after Hurricane Andrew1

Abstract: All broadleaf woody plants of pinelands and hammocks (upland areas) in the northern parts of Everglades National Park were defoliated by the strong winds of Hurricane Andrew in August 1992. Most plants re-leafed within two months of the storm, at which time we tagged newly produced leaves of eight species (five species in two hardwood hammocks and four in two pineland sites; one species was studied in both habitats), and monitored individual leaf area lost or damaged monthly for three months. We marked a secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Previous studies have also found evidence for increased herbivory following hurricanes (Hunter and Forkner 1999, Hirsh and Marler 2002, Spiller and Agrawal 2003, Agrawal and Spiller 2004, Nakamura et al 2005, suggesting that this pattern may be fairly common (for exceptions see Schowalter and Ganio 1999, Koptur et al 2002, Angulo-Sandoval et al 2004. Studies by Spiller and Agrawal (2003) and Agrawal and Spiller (2004) on the same subject species (C. erectus) as the present study, but in a different region of the Bahamas (Exuma), revealed that following Hurricane Lili both herbivore abundance and leaf damage were higher on severely damaged than on undamaged plants and that enhanced herbivory was associated with increased leaf nitrogen and other traits that may increase foliage susceptibility to herbivores.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have also found evidence for increased herbivory following hurricanes (Hunter and Forkner 1999, Hirsh and Marler 2002, Spiller and Agrawal 2003, Agrawal and Spiller 2004, Nakamura et al 2005, suggesting that this pattern may be fairly common (for exceptions see Schowalter and Ganio 1999, Koptur et al 2002, Angulo-Sandoval et al 2004. Studies by Spiller and Agrawal (2003) and Agrawal and Spiller (2004) on the same subject species (C. erectus) as the present study, but in a different region of the Bahamas (Exuma), revealed that following Hurricane Lili both herbivore abundance and leaf damage were higher on severely damaged than on undamaged plants and that enhanced herbivory was associated with increased leaf nitrogen and other traits that may increase foliage susceptibility to herbivores.…”
Section: Discussionmentioning
confidence: 94%
“…, Koptur et al . ) by assuming that all living trees would have started to produce leaves and/or shoots two months after the hurricanes. Hence, trees without green leaves or shoots were recorded as deceased.…”
Section: Methodsmentioning
confidence: 99%
“…Koptur et al . studied herbivory on plants immediately following Hurricane Andrew in south Florida, which was a Category 5 storm that caused catastrophic damage.…”
Section: Other Case Studies Of Food Webs Impacted By Disturbancesmentioning
confidence: 99%